Ishkālīyāt al-Intimā’ al-Waṭanī ‘inda al-Muhājirīn al-Ḥaḍārimah fī Indūnīsīyā fī al-Niṣf al-Awwal min al-Qarn al-‘Ishrīn - Yahya Mohamed Ahmed Ghaleb (Studia Islamika, 2015)
In the early years of the twentieth century, the Hadrami community showed interest in the place from where their ancestors came to Indonesia. This research aims to analyze these historical events and provide logical interpretations of them. It relies on historical and contemporary documents, especially newspapers issued by the Hadrami community in Indonesia. It also identifies factors, causes and consequences of these events through many tracks. First, it extrapolates  the development of the community from the beginning of the twentieth century, when Hadrami nationalist ideas and feelings of belonging to the Hadrami homeland appeared. Secondly, it identifies the reasons behind that, the factors that helped its spread and the problems that resulted from these events. Thirdly, the research explores the status of the community after the outbreak of this problem and the nature of the relationship between the two groups during the subsequent years until the Japanese occupation of Indonesia in 1942. Finally, it studies the impact on the future of the Hadrami community in Indonesia.DOI: 10.15408/sdi.v22i3.2355